The efficiency dependance of a single-circuit power unit with a helium-cooled reactor and ahydrogen module on the degreeof regeneration; Eurasian Physical Technical Journal; Vol. 22, No. 1 (51) - Nurym K. Kazybek; Antonova A. M. Aleksandra Mikhailovna; Sakipov K. E. Kamalkhan Erkeshevich; Vorobiev A. V. Aleksandr Vladimirovich; Stetsov N. V. Nikolay Valerjevich (2025, 2025)
Title screen